2016
DOI: 10.12740/app/65192
|View full text |Cite
|
Sign up to set email alerts
|

Body size attitudes and body image perception among preschool children and their parents: a preliminary study

Abstract: SummaryObjective: The objectives of our study were two fold: (1) to assess body attitudes among children and their parents, and (2) to analyze the predictors of body attitudes in both groups. Method:The research sample consisted of 37 children, aged between 3 and 7, and 37 parents. We used the Sociocultural Attitudes Towards Appearance Questionnaire-4, the Child Figure Arrays, and the Contour Drawing Rating Scale.Results: Twenty-eight children (75.68%) chose the thin and average silhouettes as the ideal body s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
5
1
3
Order By: Relevance
“…Some studies highlight an increase in mean body dissatisfaction scores in men ( Holland and Tiggemann, 2016 ; Karazsia et al, 2017 ). This increase could be reflected by the prediction of children’s body dissatisfaction ( Kościcka et al, 2016 ). However, in part, this was not verified in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies highlight an increase in mean body dissatisfaction scores in men ( Holland and Tiggemann, 2016 ; Karazsia et al, 2017 ). This increase could be reflected by the prediction of children’s body dissatisfaction ( Kościcka et al, 2016 ). However, in part, this was not verified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As such, many studies have focused on linking eating behaviors and parental physical activity to the risk of being overweight in children ( Matthews-Ewald et al, 2015 ). The authors found that, in a sample of children aged 3–7 years, parental dissatisfaction as assessed by a silhouette scale correlated with child dissatisfaction ( Kościcka et al, 2016 ). Similarly, Webb and Haycraft (2019) highlight the link between body dissatisfaction and disadaptative eating habits of parents and the body dissatisfaction of children aged 6–9 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the parents of the children can more easily relate the similar styles of each season in the clothes of children and adults. This observation carries with it a danger already pointed out in the bibliographic review: the fact that parents do not contribute to reversing the possible negative influences on their children produced by the thin advertising stereotype (Kościcka, Czepczor & Brytek-Matera, 2016). If, as has been observed, this point-of-sale advertising is also directed at parents, they must possess a strong critical capacity to consciously reject such models and foster a healthy attitude towards their children.…”
Section: Resultsmentioning
confidence: 87%
“…Imagem Corporal numa perspetiva lifespan © de si (Kościcka et al, 2016), podem influenciar a forma como as crianças desenvolvem a sua imagem corporal. Por exemplo, quando os membros da família demostram uma postura negativista perante a obesidade, as crianças tendem a partilhar as mesmas opiniões (Duarte et al, 2018).…”
Section: Infânciaunclassified